Empathy for patient care in medical students: new evidence on the importance of self-transcendence. Issue 5 (28th May 2022) - Miniotti, Marco
ABSTRACT: Empathy is essential in clinical care to achieve patient satisfaction, treatment adherence and health outcomes. Understanding how personality traits might influence the development of medical students' empathy for patient care is important in medical education. Previous studies have shown associations between medical students' personality and empathy. This study aims to explore the associations between temperament and character and empathy for patient care in a sample of young medical students. Participants were 299 second-year Italian medical students. They completed the Italian versions of the Jefferson Scale of Empathy for medical students (JSE-S) and the Temperament and Character Inventory (TCI-140). Correlation and regression analyses were performed. Significant positive low correlations were found between empathy and Reward Dependence, Cooperativeness and Self-transcendence. The regression model of the sex and personality dimensions explained 14% of the variance in empathy with two significant predictors: sex (B = 4.034) and Self-transcendence (B = 0.361). This study confirms that female medical students are more empathetic than males. It also suggests that the greater students' Self-transcendence is, the more empathetic towards patient care they are. Attention to medical students' personality should be present within medical curricula, as it may help to generate methods of enhancing and sustaining the empathy of students.